2000
DOI: 10.1007/s005950050616
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced graft healing of high-porosity expanded polytetrafluoroethylene grafts by covalent bonding of fibronectin

Abstract: The effect of covalent bonding of fibronectin on the patency and graft healing of high-porosity expanded polytetrafluoroethylene (ePTFE) grafts was evaluated. Bilateral carotid grafting was performed in ten mongrel dogs using high-porosity (60 microm) ePTFE grafts, 4 cm in length and 4 mm in internal diameter, that either had been pretreated by the covalent bonding of fibronectin (fibronectin grafts) or were untreated (control grafts). The grafts were harvested 4 to 6 weeks after surgery and subjected to macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…Our preliminary studies on long-fibril ePTFE grafts in canine and porcine models demonstrated that the fibronectin-bonded graft exhibited better graft healing than the nonbonded control graft in the short term of 3-6 weeks. 10,11 We designed this study based on the evaluation and performance standards for arterial prostheses described by Abbott et al 15 We used the canine iliofemoral-tofemoral artery model with a prosthesis 10 cm long and 4 mm in diameter because the paired-site test is feasible and the flow is similar to the femoral artery flow in humans. The improved neointima formation seen in the fibronectin-bonded grafts was not seen in the nonbonded control grafts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our preliminary studies on long-fibril ePTFE grafts in canine and porcine models demonstrated that the fibronectin-bonded graft exhibited better graft healing than the nonbonded control graft in the short term of 3-6 weeks. 10,11 We designed this study based on the evaluation and performance standards for arterial prostheses described by Abbott et al 15 We used the canine iliofemoral-tofemoral artery model with a prosthesis 10 cm long and 4 mm in diameter because the paired-site test is feasible and the flow is similar to the femoral artery flow in humans. The improved neointima formation seen in the fibronectin-bonded grafts was not seen in the nonbonded control grafts.…”
Section: Discussionmentioning
confidence: 99%
“…9 Covalent bonding of fibronectin was prepared as described previously. 10 The grafts were treated with a mixed solution of methyl lithium and hexamethyl phosphoric amide (Aldrich Chemicals, Milwaukee, WI, USA) in argon gas at 0°C for 30 min, leaving the surface defluorinized. This was followed by treatment with methacrylic acid (Wako Pure Chemicals, Osaka, Japan) at 80°C for 4 h. The methacrylic acid was polymerized to the defluorinized surface.…”
Section: Graft Characteristics and Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until 10 years ago, approximately 90% of prostheses in large animal models were as short as 5.571.2 cm (Dacron and expended polytetrafluoroethylene (ePTFE)) and 4.571.7 cm polyurethanes (PU), with a median implantation periods of 91.8717.3 days for Dacron grafts, 60.079.36 days for polytetrafluoroethylene (PTFE) grafts [11] and 907127.1 days for PU grafts. In more recent years, slightly longer grafts were implanted (64% were still shorter than 7 cm) and observation periods became shorter (medians: 28.078.9 and 14.0718.7 for ePTFE and Dacron, respectively) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. In the small proportion of studies where truly long prostheses were implanted, they were either aorto-aortic [30][31][32][33][34][35], aorto-iliac [36][37][38][39] or aorto-femoral [40].…”
Section: Transanastomotic Endothelialization (Tae): Barking Up the Wrmentioning
confidence: 99%
“…Coating the inner surface with a thin layer of proteins (e.g. fibronectin) [9,10] is an effective method to enhance the autologous endothelialization of PTFE-based vascular grafts. As a result, the risk of thrombosis of small-caliber prosthesis is limited.…”
Section: Introductionmentioning
confidence: 99%